Prevalence of programmed death ligand-1 in patients diagnosed with non-small cell lung cancer in Lebanon. (September 2021) - Fakhri, Ghina; Akel, Reem; Khalifeh, Ibrahim; Chami, Hassan; Hajj Ali, Adel; Al Assaad, Majd; Atwi, Haneen; Kadara, Humam; Tfayli, Arafat
Introduction: Programmed death ligand-1 expression has been shown to be a good predictor of response to cancer therapy with checkpoint inhibitors. Its expression varies among different tumor types and among non-small cell lung cancer patients with different clinical and demographic characteristics. The prevalence and determinants of programmed death ligand-1 expression have been previously reported from various regions of the world, but data from Lebanon are lacking. This study examines the prevalence and the clinical, demographic and pathological predictors of programmed death ligand-1 expression in patients diagnosed with non-small cell lung cancer in Lebanon. Methods: Medical records of 180 patients diagnosed with primary non-small cell lung cancer at our institution and tested for programmed death ligand-1 expression were reviewed. Clinical, demographic and pathological information were collected and correlated with programmed death ligand-1 expression using the chi-square test and logistic regression. Results: One hundred eleven of the 180 non-small cell lung cancer tumor samples tested positive for programmed death ligand-1 expression (61.7%). 27.2% of those tumor samples expressed programmed death ligand-1 in 1%–49% of tumor cells, while 34.4% of tumor samples expressed programmed death ligand-1 in 50% or more of their cells. Squamous histology and advanced stage were significant predictors of programmed death ligand-1 expression (odds ratio = 2.79, 95% confidence interval [1.13–6.90], p = 0.012 and odds ratio = 2.48, 95% confidence interval [1.23–4.99], p = 0.044, respectively). Conclusion: Similar to reports from other populations, our results suggest that programmed death ligand-1 expression in non-small cell lung cancer is highly prevalent in the Lebanese population, especially in patients with advanced stage at diagnosis or squamous cell carcinoma histology. Because of the small sample size, while more that 60% of the patients are Lebanese, the results of this article cannot be extrapolated to the Middle Eastern and the Levantine population.